FIRMS SPECIFIC CHARACTERISTICS AND QUALITY FINANCIAL REPORTING OF UNIVERSAL BANKS LISTED ON THE STOCK EXCHANGES OF SELECTED AFRICAN COUNTRIES (Journal of Global Accounting, 2023)
The increasing failure of universal banks across different countries on the African Continent has made it imperative to advocate for increased financial reporting quality as well as stronger management control through creation of reliable firm characteristics. The paper, therefore, evaluates firm’s characteristics and quality financial reporting of universal banks listed on the stock exchanges of selected countries in Africa comprising Nigeria, South Africa and Ghana. Specifically, the study intends to determine the extent to which firm leverage and firm size affect financial reporting of universal banks in stock exchanges of selected African Countries.          It also aims at evaluating the effects of the level of firm profitability impact on the financial reporting quality of Universal banks in the stock exchanges of selected African countries. The ex-post facto research design was employed using the multiple regression technique to analyze the thirteen years of pre and post IFRS reporting periods’ data collected from published annual reports of selected universal banks from Nigeria ( 2005-2018), South Africa (200b3-b2016)and Ghana (2000 - 2013). Findings from the analysis established that the Firms Leverage and Firm Size have significant positive effect on financial reporting quality of selected commercial banks in Nigeria, South Africa and Ghana for pre and post IFRS reporting periods. The study also established that firms’ profitability had significant positive effect on the financial reporting quality of commercial banks in Nigeria, South Africa and Ghana for the Pre and Post IFRS reporting periods. The study therefore recommends that commercial banks in Nigeria, South Africa, and Ghana should manage their debt (leverage) level and firm size so as to further enhance managers’ ability to ensure credible reportage of the annual activities of the banks.  The study further recommends that commercial banks in Nigeria, South Africa, and Ghana should strive to ensure optimum profitability since firms with a high level of profitability tend to be fair in their reporting.
Keywords: Financial Reporting Quality; Firm Structure; Universal Banks